Two children with a woman on Islamorada, Florida (2/8/1957-2/15/1957) (Tufts Archival Research Center, 2005)
2-1/2 x 3-1/2. Photos taken during Edward R. Murrow's trip to Florida to interview Harry S. Truman for See It Now, which aired 2/2/1958